Simultaneously enhance the inactivation and inhibit the photoreactivation of fungal spores by the combination of UV-LEDs and chlorine: Kinetics and mechanisms. (1st October 2020) - Wan, Qiqi; Wen, Gang; Cao, Ruihua; Zhao, Hui; Xu, Xiangqian; Xia, Yuancheng; Wu, Gehui; Lin, Wei; Wang, Jingyi; Huang, Tinglin
Abstract: Waterborne fungi have been recognized as an emerging environmental contaminant in recent years. This work was to investigate the inactivation efficiency and mechanisms of ultraviolet light-emitting diodes (UV-LEDs)/chlorine (Cl2 ) (265, 280 and 265/280 nm combination) and LPUV/Cl2 (254 nm) treatments for three fungal species compared with individual disinfection processes. Control of photoreactivation for fungal species inactivated by UV-LEDs/Cl2 and LPUV/Cl2 was also evaluated. The results revealed that the combined UV-LEDs/Cl2 and LPUV/Cl2 processes, especially UV-LEDs/Cl2, exhibited better inactivation performance compared to UV alone and Cl2 alone based on the inactivation rate constants, and an evident synergistic effect was observed. For example, the inactivation rates for Penicillium polonicum in the processes of UV265 /Cl2, UV280 /Cl2, UV265/280 /Cl2 and LPUV/Cl2 was 0.142, 0.168, 0.174 and 0.106 cm 2 /mJ, respectively, which were all approximately 1.5-fold higher than that of UV alone. The synergistic effect of fungal spores inactivation by UV-LEDs/Cl2 and LPUV/Cl2 was due to the high level production of intracellular reactive oxygen species and the reaction of potential extracellular free radicals. Resistance of the tested fungal spores was as follows: Trichoderma harzianum < Penicillium polonicum < Aspergillus niger . In addition, the joint effect of DNA and other cellular damage resulted in the inhibition of photoreactivation of fungal spores inactivated by UV-LEDs/Cl2 and LPUV/Cl2 compared with that of fungal spore inactivated by UV alone. This study may provide reference for controlling the dissemination of waterborne fungi utilizing combined UV-LEDs and free chlorine processes. Graphical abstract: Image 1 Highlights: The combination of UV and Cl2 exhibited better performance than individual processes. There were synergistic effects in the inactivation of P. polonicum and T. harzianum by UV-LEDs/Cl2 . UV-LEDs/Cl2 performed better inactivation efficiency than that of LPUV/Cl2 . Joint effect of DNA damage and other cellular injuries lead to the inhibition of photoreactivation.